Predicting Success: Left Ventricular Assist Device Explantation Evaluation Protocol Using Comprehensive Cardiopulmonary Exercise Testing. (January 2017) - Steiner, Johannes; Wiafe, Stephanie; Camuso, Janice; Milley, Katherine; Wooster, Luke T.; Bailey, Cole S.; Thomas, Sunu S.; D'Alessandro, David A.; Garcia, Jose P.; Lewis, Gregory D.
Abstract : Supplemental Digital Content is available in the text.